High-Sensitivity Troponin I and Incident Coronary Events, Stroke, Heart Failure Hospitalization, and Mortality in the ARIC Study. Issue 23 (4th June 2019) - Jia, Xiaoming; Sun, Wensheng; Hoogeveen, Ron C.; Nambi, Vijay; Matsushita, Kunihiro; Folsom, Aaron R.; Heiss, Gerardo; Couper, David J.; Solomon, Scott D.; Boerwinkle, Eric; Shah, Amil; Selvin, Elizabeth; et al.
Abstract : Background: We assessed whether plasma troponin I measured by a high-sensitivity assay (hs-TnI) is associated with incident cardiovascular disease (CVD) and mortality in a community-based sample without prior CVD. Methods: ARIC study (Atherosclerosis Risk in Communities) participants aged 54 to 74 years without baseline CVD were included in this study (n=8121). Cox proportional hazards models were constructed to determine associations between hs-TnI and incident coronary heart disease (CHD; myocardial infarction and fatal CHD), ischemic stroke, atherosclerotic CVD (CHD and stroke), heart failure hospitalization, global CVD (atherosclerotic CVD and heart failure), and all-cause mortality. The comparative association of hs-TnI and high-sensitivity troponin T with incident CVD events was also evaluated. Risk prediction models were constructed to assess prediction improvement when hs-TnI was added to traditional risk factors used in the Pooled Cohort Equation. Results: The median follow-up period was ≈15 years. Detectable hs-TnI levels were observed in 85% of the study population. In adjusted models, in comparison to low hs-TnI (lowest quintile, hs-TnI ⩽1.3 ng/L), elevated hs-TnI (highest quintile, hs-TnI ≥3.8 ng/L) was associated with greater incident CHD (hazard ratio [HR], 2.20; 95% CI, 1.64–2.95), ischemic stroke (HR, 2.99; 95% CI, 2.01–4.46), atherosclerotic CVD (HR, 2.36; 95% CI, 1.86–3.00), heart failure hospitalization (HR, 4.20; 95% CI, 3.28–5.37), global CVD (HR, 3.01; 95% CI, 2.50–3.63), and all-cause mortality (HR, 1.83; 95% CI, 1.56–2.14). hs-TnI was observed to have a stronger association with incident global CVD events in white than in black individuals and a stronger association with incident CHD in women than in men. hs-TnI and high-sensitivity troponin T were only modestly correlated ( r =0.47) and were complementary in prediction of incident CVD events, with elevation of both troponins conferring the highest risk in comparison with elevation in either one alone. The addition of hs-TnI to the Pooled Cohort Equation model improved risk prediction for atherosclerotic CVD, heart failure, and global CVD. Conclusions: Elevated hs-TnI is strongly associated with increased global CVD incidence in the general population independent of traditional risk factors. hs-TnI and high-sensitivity troponin T provide complementary rather than redundant information. Abstract : Supplemental Digital Content is available in the text.